Implementasi Plea Bargaining System Kedalam Pembaharuan Sistem Peradilan Pidana Tindak Pidana Korupsi - Pratiwi, Novianti (Kajian Ilmiah Hukum dan Kenegaraan, 2023)
Purpose: This paper aims to provide information and knowledge to readers regarding the implementation of the Plea Bargaining system in the reform of the criminal justice system in tipikor cases. Research methodology: The study uses a normative legal method, which is research that examines document studies using a legislative approach, where this approach reviews all laws and regulations related to the plea bargaining system in the criminal justice system in Indonesia, which are relevant to the legal issues being raised. Results: the results of the research in this study is, The idea of using plea bargaining in an effort to reform the criminal justice system in Indonesia in corruption cases can be found on philosophical grounds based on the 5th principle of Pancasila. which efforts aim to create a judicial principle that is simple, fast and low cost. Limitations: This writing raises the formulation of the problem, namely how the application of the Plea Bargaining system idea can be implemented in an effort to reform the criminal justice system in corruption cases in Indonesia Contribution: The writing of this article is intended for law enforcers and lawmakers so that plea bargaining can be applied in the criminal justice system in Indonesia and provide a sense of justice and the completion of cases that are fast simple and low cost.